Kolaborasi Aktor dalam Pengelolaan Sampah di Tempat Pembuangan Akhir (TPA Alak) - Jessica. A. P. Sari. Fm; William Djani; Made N. D. Andayana; Maria M. Lino (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to find out the collaboration of actors in waste management in landfills (TPA). This study uses descriptive research using qualitative research methods and using Ratner's (2012) theory which includes Identification of Barriers and Opportunities, Debate Strategies to Influence, and Collaborative Action Planning. There were 5 informants in this study. The results of the study show that the collaboration that occurs in waste management has gone well, but there are still obstacles in overcoming existing problems. To identify obstacles and opportunities, there are situations and needs as well as resources that must be met, the collaboration that occurs between the Environment and Hygiene Agency and the head of waste management and b3 waste has been running but is not optimal enough due to the lack of resources in facilitating infrastructure facilities at landfills. Debate strategies to influence and increase public awareness and understanding require socialization related to understanding how to manage waste properly. The Head of the Environment and Hygiene Agency together with the Head of the B3 Waste Management Division have collaborated with the Mutiara Timor Waste Bank in providing effective socialization to reduce the volume of existing waste, but many people do not understand the socialization. Planning this cooperation action, there is a collaborative implementation strategy where the actors collaborate in planning the right implementation strategy to reduce the volume of waste in the landfill, but the collaboration between the Head of the Environment and Hygiene Agency and the Mutiara Timor Waste Bank has targeted 20% in handling the volume of waste, but the cooperation is only 5% that can reduce the volume of waste in the landfill because the socialization provided is still not understood by the Public. For the purpose and purpose of this cooperation is the target in reducing and handling waste from 2018-2025, if this cooperation runs effectively and successfully, slowly the volume of waste in landfills will decrease by itself.